Эмпирическое исследование уровня рефлексивности и гибкости поведения учителей средней школы - Ostapenko, Karina (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2015)
The publication content includes the description of methodology and results for empirical research of relationship between secondary school teachers reflexivity and flexibility of behavior. The objective of the research is to describe and to explain the relationship character and mechanisms between reflexivity and flexibility of behavior. The materials used: reflectivity level determination method (А.В. Карпов, В.В. Понаморева, 2000); and the scale «flexibility of behavior» from the self-actualization test (САТ) (Personal Orientation Inventory – POI; 1987, E. Shostrom, modified by E. Alyoshina, L. Gozman, M. Zagik, M. Kroz). Theselection was defined and reasoned. The achieved empirical data was processed with SPSS 17 software. The results were analyzed and interpreted. Relationship between reflexivity and flexibility of behavior was stated. 80 school teachers were recruited for this research: a group of 30-40-year old people (40 people; age median 37 years) and a group of 50-60-year old people, (40 people; age median 56 years).